Stadialność rozwoju zawodowego człowieka. Odniesienia empiryczne - Piorunek , Magdalena (Studia Edukacyjne, 2020)
The paper “Stadialność rozwoju zawodowego człowieka. Odniesienia empiryczne” [Career Development Stages. Empirical References] refers to Donald Super’s classic career development theory that emphasizes the life-long and sequential nature of the process. D. Super defined five career development stages, i.e. growth, exploration, establishment and stabilization, maintenance (consolidation) of one’s professional position, and decline. Though, generally, the division of the career development into stages and the related sequential modern career model are still relevant, D. Super’s time frames have changed, career development stages are being modified, and their constituents are in the process of diffusion. With the linear career narrative being challenged, the long adulthood is when the major changes occur, i.e. frequently career commitment cycles break and end more quickly, and day often repeatedly reemerge over one’s vocational life, while individuals, due to the de-standardization of the career development, are made to tailor their careers in response to their dynamically changing personal needs and current labor market demands. The selected theses and conclusions presented in this paper and drawn from studies conducted following various methodological strategies over a number of years, describe the regularities observed in the subsequent career development stages, extending from childhood, through adolescence to the adulthood phases. The paper identifies selected patterns of developing dream “career projects” in childhood, career planning strategies in adolescence, perception of the post-modern career paradigm in early adulthood, and the main career patterns pursued in middle adulthood. These patterns and regularities illustrate the specific features of the individual’s career development stages.